The Hellenistic terracottas from Demetrias - Ieremias, S (2019)
This thesis provides a first contextual study of the terracottas from Hellenistic Demetrias. Focusing on the finds from the sanctuaries of the city (the Sanctuary of Pasikrata, of the Mother-of-the-Gods, the “Thesmophorion” and the Favissa on Hill 35), from the Anaktoron, from a Hellenistic house, and from the cemeteries, it covers the whole spectrum of life in the city, public and private, cultic and funerary. The material is presented by context, as it informs our understanding of the terracottas’ use and meaning. The main questions that this thesis addresses are the following: a) how typical was Demetrias as a Hellenistic city, through its terracottas? b) what can we learn about their use in the city? c) were specific types used in specific contexts? d) what can we learn about the cults and rituals in the city through the terracottas? e) what can we discern about workshops in the city? f) what can we learn about trade through the terracottas? g) did the coroplastic repertoire follow the general trends of the Hellenistic period? In order to address these questions, the thesis also focuses on re-contextualising the coroplastic material from the city that was considered lost (Sanctuary of Pasikrata, Sanctuary of the Mother-of-the-Gods, South Cemetery).